Analisis Wacana Kritis Berita Politik dalam Surat Kabar Koran Kaltim - Alfira, Jihan; Mulawarman, Widyatmike Gede; Rijal, Syamsul (Universitas Mulawarman, 2019)
This study aims to describe the form of language expression and the political news discourse perspective of Koran Kaltim using Roger Fowler's model. In using Roger Fowler's analysis, clarification can be seen how the same event is translated into different languages. These different words are not seen as technical but are seen as an ideological practice. This type of research is a qualitative descriptive study. Sources of data used in this research are journalistic products of printed mass media, namely Koran Kaltim. Data collection techniques are reading, listening, and note-taking techniques. The data presentation technique in this study contains an explanation of the forms of language expression and perspective. Overall the results of the study show the following two conclusions. First, the forms of language expression based on political news discourse modalities include necessity modality, desire modality, truth modality as well as various types of metaphors. This form of language expression represents the views, values, ideas and beliefs of journalists in the Kaltim newspaper. Second, the pro-government perspective dominates the political news in the Kaltim newspaper.